ANALISIS PENGARUH INFLASI, SUKU BUNGA (SB) DAN INVESTASI TERHADAP JUMLAH UANG BEREDAR (JUB) DI INDONESIA TAHUN 1991 - 2022 - Ahmad Al Hafizh (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2022)
The purpose of this study was to determine the effect of inflation, interest rates and investment on the money supply in Indonesia from 1991 to 2021. The money supply (JUB) is the total value of money in the hands of the public, consisting of currency and demand deposits. Theoretically, the money supply will affect the value of money implemented at the price and product levels. Factors that affect the money supply are income, inflation, interest. Therefore, the method that can be used is the Error Correction Model (ECM). and the data used is quantitative data, because the data is used to calculate the effect on the variable amount of money in circulation. The data source used is in the form of secondary data, which is data obtained from official sites or websites. The results of this study are that the variable inflation and interest rates have a significant effect on the amount of money in circulation, then the investment variable has no effect and is not significant on the amount of money in circulation